Penataan Kawasan Nelayan Insit Kepulauan Meranti Dengan Pendekatan Arsitektur Tepian Air - M Iswandi; Mira Dharma Susilawati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Insit Fishermen Area is a fisherman settlement area that is less organized and has no tourist attraction. Whereas Insit Fishermen Area is an entrance gate to Meranti island through Ro-Roport. Therefore, it is necessary to arrange the area of fishermen by adding more facilities and infrastructure, not only to support the activities of fishermen but also for tourist attraction. This arrangement also looks for the feasibility standard of facilities, infrastructure, and the dominantaspects of waterfront architecture and its elements. The design method used is the results of the survey, documentation, and analysis of qualitative and quantitative data. The results of thisarrangement applying the concept of “Insit With The Flow”. The arrangement of the area follows the flow of the Insit tributary, which is the result of the applying elements of the concept and waterfront architecture theme. This arrangement utilizes the river as a circulation in and out of fishing boats, and on the riverside, there is a Promenade/Esplanade, seats, and parks. Thisarrangement will function as a fishing, commercial, recreational and public open space for local people and tourists.Keywords: Insit, Kepulauan Meranti, Fishermen Area, Waterfront Architecture, With The Flow